Agenda-setting in the realm of popular culture: The case of the Korean Wave in East Asia - Jung, Hyeri (Global Media and Communication, 2019)
The spread of South Korean popular culture across the globe, known as the Korean Wave, has signalled a significant challenge towards the traditional one-way flow of media culture. This study applies agenda-setting effect, which has been largely applied to political communication, to the domain of mass-produced popular culture. It explores how Korean media’s news coverage of the popularity of Korean TV drama in China influences not only the first and second agenda-setting effect but also Koreans’ perception of Chinese audiences. The findings suggest that the Korean Wave could serve as a form of reversed cultural diplomacy by promoting soft power in East Asia.
https://katalog.adlr.link/Record/ai-49-aHR0cDovL2R4LmRvaS5vcmcvMTAuMTE3Ny8xNzQyNzY2NTE5ODcyNzgy